Phosphodiesterases S-sulfhydration contributes to human skeletal muscle function. - Valentina Vellecco; Elisabetta Panza; Sofia-Iris Bibli; Gian Marco Casillo; Federica Raucci; Onorina Laura Manzo; Martina Smimmo; Romolo Villani; Maria Rosaria Cavezza; Ingrid Fleming; Roberta d'Emmanuele di Villa Bianca; Francesco Maione; et al. (Pharmacological Research, 2022)
The increase in intracellular calcium is influenced by cyclic nucleotides (cAMP and cGMP) content, which rating is governed by phosphodiesterases (PDEs) activity.Despite it has been demonstrated a beneficial effect of PDEs inhibitors in different pathological conditions involving SKM, not much is known on the role exerted by cAMP-cGMP/PDEs axis in human SKM contractility. Here, we show that Ssulfhydration of PDEs modulates human SKM contractility in physiological and pathological conditions. Having previously demonstrated that, in the rare human syndrome Malignant Hyperthermia (MH), there is an overproduction of hydrogen sulfide (H2S) within SKM contributing to hyper-contractility, here we have used MH negative diagnosed biopsies (MHN) as healthy SKM, and MH susceptible diagnosed biopsies (MHS) as a pathological model of SKM hypercontractility. The study has been performed on MHS and MHN human biopsies after diagnosis has been made and on primary SKM cells derived from both MHN and MHS biopsies. Our data demonstrate that in normal conditions PDEs are S-sulfhydrated in both quadriceps’ biopsies and primary SKM cells. This post translational modification (PTM) negatively regulates PDEs activity with consequent increase of both cAMP and cGMP levels. In hypercontractile biopsies, due to an excessive H2S content, there is an enhanced Ssulfhydration of PDEs that further increases cyclic nucleotides levels contributing to SKM hyper-contractility. Thus, the identification of a new endogenous PTM modulating PDEs activity represents an advancement in SKM physiopathology understanding.